Longevity and fecundity of Colasposoma dauricum Mannerheim (Coleoptera Chrysomelidae: Eumolphinae), a pest of sweet potato in Korea - Alaijos, Oliver R.; Lee, Jong Eun (2005)
The adult longevity and reproductive biology of Colasposoma dauricum were studied in the laboratory. Results showed no significant difference between male and female mean longevity (22.24 d and 22.50 d, respectively). Mean fecundity was 154.77 and 208.00 at 24 C and 28 C, respectively; mean number of eggs per day per female was 30.08 and 34.79 at 25 C and 28 C, respectively. Mean incubation period was 9.74 d at 25 C and 8.37 d at 28 C; 67.00% and 85.09% of the eggs hatched at 25 C and 28 C, respectively.
Keywords: Beetles; Insect pests